Are Rich Countries Immune to the Resource Curse? Evidence from Norway's Management of Its Oil Riches - Erling Røed Larsen (Statistics Norway, Research Department, 2003)
Growth studies show, counter to intuition, that the discovery of a natural resource may be a curse rather than a blessing since resource-rich countries grow slower than others. But it has been suggested that Norway may be an important exception to the curse and that the curse does not afflict rich countries. This article addresses both issues, and introduces a new diagnostic test. Neighbor countries Denmark and Sweden are used to highlight Norway's relative development and to test for curse presence. I employ a structural break technique to demonstrate that Norway started an acceleration in the early 70s, after having discovered oil in 1969, and did not experience a pronounced retardation for the next 25 years. Instead, after first catching-up with its neighbors, Norway maintained a higher pace of growth. Norway might have escaped the curse. However, data suggest a slow-down at the end of the period, opening the possibility of a late onset of the curse. If so, rich countries are not immune.
Keywords: C22; N10; O10; Q33; 330; booming sector; catch-up; counterfactual development; economic parity; economic growth; gross domestic product; immunity; natural experiment; natural resource curse; oil discovery; structural break